Oxidative Stress in Animals and the Balance Between Reactive Oxygen Species Production and Antioxidant Systems - Mohammed, Asmaa Jamal (American Journal of Bioscience and Clinical Integrity, 2026)
Oxidative stress which results from the imbalance between reactive oxygen species (ROS) generation and antioxidant defense is a fundamental issue influencing animal health and productivity. Excessive ROS can cause oxidations of lipids, proteins and DNA, which results in growth retardation, reproductive depression, immunosuppression of animals and low quality of animal products. In this review, the main sources of ROS will be addressed along with how they play a role in oxidative stress in biological systems and how antioxidant defenses - both enzymatic and non-enzymatic -come into play. Regular management strategies and environment are identified as effective measures to counteract oxidative stress, as well as based nutritional interventions (i.e., vitamins, trace elements and phytochemicals). Furthermore, recent techniques of biomarkers and molecular diagnosis allow the early detection, the phytoplanktic redox imbalance as well as species specific management. The balance between ROS and the antioxidant system is absolutely necessary to optimize growth, reproduction, immune status, and product quality in animals. Further studies are required for the optimization of interventions and to explore new biomarkers in order to more accurately assess oxidative stress.